A new freshwater gobiid species of Rhinogobius Gill, 1859 (Teleostei: Gobiidae) from northern Taiwan - Chen, I-Shiung; Wang, Shen-Chih; Shao, Kwang-Tsao (Zootaxa, 2022)
A new freshwater rhinogoby has been collected and surveyed from northern Taiwan. The new species, Rhinogobius yangminshanensis n. sp. with fluvial life history can be well distinguished from other congeners by the following combination of features: (1) fin rays: second dorsal fin rays I/9; anal fin rays I/8; pectoral fin rays modally 16; (2) squamation: longitudinal scale series 28–30 (modally 29); perdorsal scales 9–10 (modally 9); (4) vertebral count 27; (5) rear edge of mouth: merely extending to vertical of anterior margin of pupil in male and (6) specific colouration: lateral side with 6–7 longitudinal rows of bright orange to orange red spots in male which general size about 1/2 of pupil diameter. Cheek and opercle with 24–35 orange spots in male. Branchiostegal membrane with many minute orange spots in male. Caudal fin with distally orange zone in male with about 3 vertical rows of orange or orange red spots. First dorsal fin with broad orange band on distally 1/3 area. A middle black spot in abterior first dorsal fin. Pectoral fin with two rows red orange spots in male. The phylogenetic comparisons have revealed that the great mitogenetic differences of R. yangminshanensis with all other congeneric species and sister species would be R. rubromaculatus in Taiwan. A diagnostic key to all valid species of Rhinogobius from Taiwan is also provided.